Multiple Cell Transplantation Based on an Intraparenchymal Approach for Patients with Chronic Phase Stroke. Issue 1 (January 2013) - Chen, Lin; Xi, Haitao; Huang, Hongyun; Zhang, Feng; Liu, Yancheng; Chen, Di; Xiao, Juan
Stroke is the third leading cause of death worldwide and a huge perpetrator in adult disability. This pilot clinical study investigates the possible benefits of transplanting multiple cells in chronic stroke. A total of 10 consecutive stroke patients were treated by combination cell transplantation on the basis of an intraparenchymal approach from November 2003 to April 2011. There were six males and four females. Their age ranged from 42 to 87 years, and the course of disease varied from 6 months to 20 years. Six patients suffered cerebral infarction, and four patients suffered a brain hemorrhage. The olfactory ensheathing cells, neural progenitor cells, umbilical cord mesenchymal cells, and Schwann cells were injected through selected routes including intracranial parenchymal implantation, intrathecal implantation, and intravenous administration, respectively. The clinical neurological function was assessed carefully and independently before treatment and during a long-term follow-up using the Clinic Neurologic Impairment Scale and the Barthel index. All patients were followed up successfully from 6 months to 2 years after cell transplantation. Every subject achieved neurological function amelioration including improved speech, muscle strength, muscular tension, balance, pain, and breathing; most patients had an increased Barthel index score and Clinic Neurologic Impairment Scale score. These preliminary results demonstrate the novel strategy of combined multiple cell therapy based on intraparenchymal delivery: it appears to be relatively clinically safe and at least initially beneficial for chronic stroke patients. This manuscript is published as part of the International Association of Neurorestoratology (IANR) supplement issue of Cell Transplantation .